Study of Alternating Transmission Performance of Shape Memory Alloy and Magneto-rheological Fluid - Gong Hang; Hu Guanghui; Hu Rongli (Jixie chuandong)
In response to the shortcomings such as the degradation of transmission performance of magneto-rheological fluid at high temperature, an alternating transmission method of shape memory alloy and magneto-rheological fluid is proposed. Based on the thermodynamic effect of the shape memory alloy, the relationship between the squeezing pressure of the spring and the temperature is derived, and the correctness of the equation is verified by experiment; the finite element analysis of the magnetic field of the transmission device is carried out, and the magnetic field distribution along the radial direction of the working gap is derived; based on the thermal driving characteristics of the shape memory alloy spring, the relationship between the friction torque and the squeezing pressure, the structure size and other parameters is established. The results show that the squeezing force generated by the shape memory alloy spring increases with the increase of temperature; when the temperature is lower than 40 ℃, the torque is mainly transferred by the magneto-rheological fluid, reaching 9.14 N·m; when the temperature is between 40 ℃ and 60 ℃, the torque is transferred by the magneto-rheological fluid and the shape memory alloy together, reaching 13.24 N·m; when the temperature is higher than 60 ℃, the torque is mainly transferred by the shape memory alloy, reaching 9.40 N·m. As the temperature rises, the shape memory alloy can transmit torque instead of the magneto-rheological fluid, and the device can sense the temperature change to realize the alternating transmission.